Learning Islamic Religious Education for Children with Special Needs at the Early Childhood Education Level - Andi Fitriani Djllong; Ahmad Ridani; Jafar Sadiq; Yance Manoppo; Wily Mohammad (Journal Emerging Technologies in Education, 2023)
Background. In essence, humans are the most perfect creatures among other creatures. Humans are created with a brain but they are given limitations in intelligence. Exceptional children today are better known as children with special needs. PAI learning for children with special needs requires professional educators. Purpose. The purpose of this study was to determine how the implementation of PAI learning for children with special needs at the PAUD level. Method. This research uses qualitative methods in order to find out reliable data research through surveys and in-depth interviews. Results But there are also obstacles such as the lack of professionalism of an educator in providing learning and still inadequate PAI learning books. Conclusion. It can be concluded that PAI learning for children with special needs at the PAUD level has gone well but still needs improvement and also the attention of the Ministry of Religion to provide PAI learning books.